(untitled) (Vietnam Journal of Community Medicine, 2025)
Objectives: Determine the epidemiological characteristics and some measles characteristics such as place of residence, age group, gender, measles vaccination status, and presentation to healthcare facilities after disease detection, in Ca Mau Province from 2015 to 2024. Research methods: Data were retrieved from the Ministry of Health’s infectious disease management software; 4461 children met the criteria for analyzing incidence, complications, and determining associations through logistic regression. Results: Males had a higher measles incidence (55.97% vs 44.03%), rural children accounted for 68.44% compared to 31.56% in urban areas. The 5 age to under 16 age group accounted for 42.43% of cases; 81.96% of children were unvaccinated. Regarding complications, rural children had a higher rate (58.11% vs 50.64%; OR = 1.35). The complication rate was highest in children under 9 months (66.15%) with a decreasing trend with age (adjusted OR = 0.74). Late hospitalization (≥ 3 days) increased the risk of complications (OR = 1.66), while vaccinated children had a lower risk (47.20% vs 57.63%; OR = 0.67). Conclusions: Factors such as gender, place of residence, age group, hospitalization time, and vaccination status significantly influence measles incidence and complications. The study emphasizes the need to strengthen vaccination programs and improve access to healthcare services, especially in rural areas, to effectively control measles, particularly in the context of the 2024 outbreak.